A dual-readout chemiluminescent-gold lateral flow test for multiplex and ultrasensitive detection of disease biomarkers in real samples. Issue 33 (4th July 2016) - Chen, Yiping; Sun, Jiashu; Xianyu, Yunlei; Yin, Binfeng; Niu, Yajing; Wang, Songbai; Cao, Fengjing; Zhang, Xiaoqing; Wang, Yu; Jiang, Xingyu
Abstract : A dual-readout chemiluminescent-gold lateral flow test for quantitative detection of disease biomarkers with an ultrahigh sensitivity at a picomolar level. Abstract : Even though the gold lateral flow test (GLFT) is low-cost and allows for point-of-care testing (POCT), its intrinsic limitations including low sensitivity and incapability of quantification significantly hinder the clinical application of GLFT for assaying disease biomarkers. To improve the performance of the GLFT without sacrificing its simplicity, we develop a chemiluminescent-gold lateral flow test (C-mode GLFT) for quantitative and multiplex detection of disease biomarkers with an ultrahigh sensitivity at a picomolar level. Horseradish peroxidase (HRP) and antibody (Ab) are simultaneously labeled onto the surface of gold nanoparticles (AuNPs) to achieve a dual-readout (chemiluminescent and visual, C&V-mode GLFT). A red color appears at the test line caused by the accumulation of captured AuNPs in the presence of targets, while HRP on the surface of AuNPs catalyzes the chemiluminescence reaction of luminol to amplify the signal. C-mode GLFT is successfully used for detecting tumor biomarkers (alpha fetoprotein, AFP, and carcino embryonic antigen, CEA) and bacterial infection biomarkers (procalcitonin, PCT) in serum samples as well as whole blood. The excellent features of C-mode GLFT such as straightforward operation, ultrahigh sensitivity and quantitative detection, make it a promising platform for POCT of a variety of disease biomarkers in real samples.